Hallazgos Macroscópicos En Necropsias Realizadas A Pericos Australianos (Melopsittacus Undulatus) En La Ciudad De Bogotá Para Orientar La Causa De Su Muerte (2021)
This project sought to obtain an exploratory analysis of the findings macroscopic in necropsies performed on dead parrots (Melopsittacus undulatus) in the city of Bogotá, to determine a possible cause of his death by observing the most common diseases, in such a way that they serve as feedback for breeders, producers and students in the determination of care to prevent specific said pathologies.The objective of this work is to establish the macroscopic changes found by means of the necropsy technique, describing the findings and attempting an approximation to the possible cause of his death, studying the most common diseases and the cause of greatest mortality in the sample budgerigars in some places of the bogota savannah, to give a vision of the most common diseases that derive from ornamental birds from modes of transmission, forms of dissemination and how to avoid them, providing a health vision that allows to the fans of the breeding of these birds, understand and know the most important measures of control of disease transmission.